Exploring the experiences of Canadian medical students with a background in the arts and humanities - Ahmed, Khadija; Patel, Arjun; Lingard, Lorelei (Canadian Medical Education Journal, 2023)
Background: Arts and Humanities (A/H) training is a powerful strategy to help medical students develop key competencies which align with the CanMEDS roles that Canadian physicians are expected to embody. Students with backgrounds in A/H may enter medical school with the skills and dispositions that A/H training provides. This paper explores the varied experiences of medical students with prior A/H backgrounds, with an emphasis on how they navigate relationships with their student cohorts and participate in undergraduate medical training environments. Methods: Descriptive qualitative research methodology was used to conduct and analyze semi-structured interviews exploring the perspectives of Canadian medical students with either a A/H degree or training in A/H (n = 13). Domains such as identity, integration of interests, and challenges in maintaining A/H interests during medical training were explored. Results: Participants described their A/H identity as intertwined with their identity as medical trainees and described their sense of interconnection between the disciplines. Challenges included imposter syndrome and difficulties in relating with peers from science backgrounds. Participants described returning to their A/H interests as a tool for wellness amidst medical training. Conclusions: Medical students with a background in A/H training describe this background as offering both affordances and challenges for their sense of identity, belonging, and wellness. These students offer an untapped resource: they come with dispositions of value to medicine, and they perceive a positive, hidden A/H curriculum that supports their maintenance of these dispositions during training. Understanding more about these hidden treasures could help foster the development of well-rounded and humanistic physicians in the entire medical class.